Short-term and long-term effectiveness of an e-coaching application; the INHERIT project. (13th November 2019) - Spelt, H; Karnaki, P; Tsiampalis, T; Kouvari, M; Petralias, A; Zota, D; Westerink, J; Linos, A
Abstract: Background: Lifestyle e-coaching applications have the potential to be successful in changing people's lifestyles although it is unclear whether such support would indeed help people with lower socioeconomic status (SES). The aim of the present study, conducted within the INHERIT EU project, was to investigate the effectiveness of a lifestyle e-coaching application in increasing physical activity (PA) in lower SES groups and whether such an increase is sustained after its prolonged use. Methods: A two-site (Greece: N = 105, Netherlands: N = 89), two arm [Greece: 50 (experimental) and 55 (control), Netherlands: 45 (experimental) and 44 (control)], parallel group, randomized controlled trial proceeded in three phases over 19 weeks, comparing PA (as measured by the IPAQ questionnaire) of participants using a lifestyle e-coaching application with participants not using any such application. Inclusion criteria involved participants to be in low SES, have an age of 18-65 years and an estimated level of physical activity of less than 210 minutes/week, while they needed to possess a smartphone, willing to install the application and being fluent in Dutch or Greek. Results: Results showed that the use of the app significantly improved participants' PA in both countries, at 6 (Greece: p = 0.015, Netherlands: p = 0.003) and 19 weeks (Greece: p = 0.002, Netherlands: p < 0.001), while the effect was even higher for low physically active participants as measured at baseline, after both time periods. Compared to the control group, after adjusting for several characteristics, the experimental group achieved a better improvement of PA at 19 weeks compared to baseline (p = 0.006) and week 6 (p = 0.007). Conclusions: Positive effects on participants' PA after 19 weeks were observed, with the findings suggesting that the longer the application is used, the greater the improvement of PA, while the effect was more obvious among those following a sedentary lifestyle as measured at baseline. Key messages: E-coaching applications could be useful in promoting physical activity among people from low SES. E-coaching applications are cost effective and environmentally friendly methods of promoting physical activity. Uptake by national health systems should be examined further.